Integrative genetic analysis reveals shared genetic architecture underlying coronary artery disease, CT-Defined coronary atherosclerosis, and cardiometabolic risk factors - Yao Zhao; Yingying Xie; Didi Wen; Jin Zhang; Ziliang Xu; Zhibin Wu; Jiaming Li; Yuanqiang Zhu; Minwen Zheng (Functional & Integrative Genomics, 2026)

Oxidative-stress-mediated apoptosis triggered by microplastics disrupts bovine oocyte maturation - Yu Wang; Jiaming Yue; Yijing Yin; Yan Zhang; Yi Zheng; Hao Jiang; Jiabao Zhang; Bao Yuan; Liang Shuang (Theriogenology, 2026)

Efficient one-pot lactic acid production from cellulose via a Trichoderma reesei and Bacillus coagulans cooperation leveraging substrate-induced secretomes - Shuai Liang; Chang Yu; Jiaming Fu; Yuanming Tao; Zhaojuan Zheng; Jia Ouyang (Bioresource Technology, 2026)

Thermally regenerable zwitterionic metal-organic frameworks with proton transfer properties for efficient lithium extraction - Xu Wu; Qian Guan; Mengyu Tang; Yue Zheng; Zhipeng Luo; Qiuyue Liu; Jiaming Gan; Xin Yu; Ranwen Ou (Chemical Engineering Journal, 2026)

Electrochemically crosslinked poly(arylene ether sulfone)-triphenylamine electrochromic polymer networks for smart windows - Keying Feng; Zhen Xing; Xiangfu Shi; Jiaming Tian; Hao Zhang; Zong-Quan Wu; Zheng Chen; Zhenhua Jiang (Chemical Engineering Journal, 2026)

Selective infrared thermal modulation device based on mixed-crystalline WO3 and electrochromic dynamic regulation technology - Jiaming Yang; Mengying Wang; Abderaouf DJEFFAL; Shukai Wang; Zheng Meng; Xinru Xu; Xungang Diao (Chemical Engineering Journal, 2026)

High-accuracy estimation of global site-level soil heterotrophic respiration through Geo-XGBoost integration with expanded datasets and remote sensing - Jie Liu; Ni Huang; Luying Zhu; Jiaming Chang; Yuting Shi; Zheng Niu; Dewen Cai; Li Wang (Agricultural and Forest Meteorology, 2026)

Humic acid-mediated activation of antimony colloid during soil redox cycles: Mechanisms and environmental implications - Xiongkai Zheng; Jiaming Xu; Haiming Cai; Qiming Mo; Yihao Li; Qixian Fu; Lijuan Zeng; Yongyang Wang; Xueqin Tao; Zhi Dang; Guining Lu (Journal of Hazardous Materials, 2026)

Molecularly functionalized high-Q THz metasurface via q-BIC for selective HbA1c detection - Chang Liu; Min Gao; Zichen Zhang; Junxiao Liu; Ligeng Jin; Xin Tian; Lijun Jiang; Zhongmei Zheng; Chuanyue Li; Jiaming Feng; Xingyu Liao; Zhihang Long; et al. (Chemical Engineering Journal, 2026)

A significantly enhanced Cu+/Cu0 catalytic active structure via the electronic effect of K for methyl glycolate synthesis - Xiaoxiao Zheng; Jiaming Wang; Peipei Lei; Qihong Xue; Xian Kan; Jiangang Chen (Chemical Engineering Journal, 2026)

Shape-dependent magnetic-driven microrobots for biofilm-eradicating medical device disinfection through mechanical and chemical bactericidal action - Ke Cheng; Tongfang Fu; Shan Sun; Wenhao Zheng; Jiaming Gong; Jingxin Ma; Yazhou Zhou; Feili Lai; Martin Pumera; Hengwei Lin (Chemical Engineering Journal, 2026)

Structural properties of two glycans in the fruits of jujube and their regulation effect of M1-type and M2-type macrophage - Jingya Ruan; Ping Zhang; Jiaming Cheng; Lequan Yu; Yijin Wu; Yinuo Zheng; Yi Zhang; Tao Wang (Carbohydrate Polymers, 2026)

The E3 ligase RNF5 facilitates viral replication by suppressing innate immune responses in grouper - Yanqi Zhao; Xiaohui Zheng; Siting Wu; Minyao Bi; Jiaming Hu; Shaojie Liu; Jingguang Wei; Qiwei Qin (Fish & Shellfish Immunology, 2026)

Different geographical patterns and assembly mechanisms of phytoplankton and benthic diatoms: a case study in a cold temperate wetland cluster - Yongxu Duan; Zhengxun Li; Jiaming Liu; Zheng Hou; Henglin Xiao; Yan Liu; Yawen Fan; Xinxin Lu (Hydrobiologia, 2026)

Effect of aquatic animal combination and their density on the removal of Microcystis aeruginosa from wastewater - Jiaming Zheng; Shanshan Xie; Xiangyong Zheng; Wenjuan Han; Min Zhao (Aquatic Ecology, 2026)

Modern pollen analysis on peatlands across monsoonal China and its implications for reconstruction - Shu Chen; Mengmeng Wang; Chunmei Ma; Tianyi Tang; Rui Ke; Jiaming Hou; Xinrong Zhang; Zhuo Zheng; Xiayun Xiao; Yan Zhao; Huayu Lu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Targeting S100A4+ macrophages to reverse radiation-induced Leydig cell fibrosis with a therapeutic nanosystem - Yewei Bao; Heng Gong; Weihao Sun; Lei Wang; Tianqi Wang; Boyang Zhang; Guanyu Ren; Shuguang Piao; Cheng Zheng; Jiaming Guo; Linhui Wang; Xinxin Gan (Chemical Engineering Journal, 2026)

Monthly Soil Respiration in China's Forests: Spatiotemporal Patterns and Drivers Over 21 Years - Jiaming Chang; Ni Huang; Li Wang; Luying Zhu; Xiaoyu Lin; Jie Liu; Zheng Niu; Dewen Cai (Global Change Biology, 2026)
Forests play a critical role as terrestrial carbon sinks in mitigating climate change. However, accurate quantification of soil respiration ( R s )—the primary CO 2 efflux from forests—remains challenging due to existing studies' overreliance on annual‐scale estimates, which obscure fine‐scale spatiotemporal dynamics and key drivers of R s . Here, we developed a 500 m resolution monthly R s dataset for China's forests (2000–2020) using remote sensing data and a geographically weighted machine learning model. A geographically weighted extreme gradient boosting model achieved the highest accuracy in predicting monthly R s ( R 2 = 0.74, RMSE = 0.8 g C m −2 day −1 ). The mean total annual R s from 2000 to 2020 was 2.32 ± 0.09 Pg C year −1 , with summer contributing most and winter least. Annual total R s and seasonal total R s showed significant increasing trends across China's forests from 2000 to 2020, with the strongest increases in southern China's young/middle‐aged natural management forests and plantations. The relationships between R s and its driving factors varied: gross primary productivity (GPP) was the primary driver of annual R s across all forest management and age classes. Seasonally, temperature dominated R s in spring/winter, and GPP dominated summer R s across all forest management and age classes, while precipitation effects varied with management/age classes and season. Our findings highlight the necessity of monthly‐scale analysis and the significant role of forest management and age in modulating R s variability.

Targeting argH to attenuate Aeromonas dhakensis virulence: A metabolic checkpoint for biofilm formation and stress adaptation - Xueqian Wang; Chenlu Yang; Xuesong Li; Wei Feng; Jianguo Zhao; Yukun Wu; Shuai Ye; Meng Zhao; Hanzeng Li; Jiaming Ju; Guiying Guo; Lixia Fan; et al. (Veterinary Microbiology, 2025)

Fiber-regulated vibration suppression and mechanical behavior of CFRP corrugated channel cored sandwich structures - Jiaming Sun; Yanlong Xu; Keyu Zhu; Leilei Yan; Xitao Zheng; Zhichun Yang (Engineering Structures, 2025)

Can we improve well‐being while reducing carbon emissions? Household‐level evidence from China - Jiaming Yu; Wenling Liu; Xiaoyan Meng; Xinzhu Zheng (Journal of Industrial Ecology, 2025)
Understanding the link between well‐being and carbon emissions is crucial, as demand‐side emission reduction efforts should not compromise living standards. While a nonlinear, threshold‐based relationship between well‐being and carbon emissions has been identified at the national level, empirical evidence at the household or individual level remains limited. Using data from the China Family Panel Studies, this study develops a multidimensional indicator framework to measure household well‐being and empirically assesses its relationship with per capita carbon emissions. The results indicate an inverted U‐shaped relationship, where carbon emissions are initially associated with improvements in well‐being. However, beyond a certain threshold, further increases in carbon emissions are no longer linked to significant gains in well‐being. Specifically, the decoupling threshold is estimated at 15.4 tons of CO 2 annually per capita in the absence of technological progress, and is reduced to 9.7 tons when technological improvements are taken into account. However, the available carbon budget is insufficient for all individuals to reach these decoupling points, and sample households could only reduce emissions by 1.4% without sacrificing overall well‐being. Moreover, prioritizing limited carbon allowances for low‐income groups may maximize societal well‐being, since their carbon intensity of human well‐being is comparatively lower. These findings underscore the importance of technological progress and population heterogeneity in designing fair and effective policies that balance well‐being with emission reductions.

Study on membrane electrolysis for the removal of Fe from the leachate of coal fly ash - Shuwei Lan; Youjian Yang; Zhaowen Wang; Yanchen Zheng; Jiaming Li; Qianhan Zhao; Tingting Liu (Journal of Environmental Chemical Engineering, 2025)

ADAM17 promotes colorectal cancer migration and invasion by regulating the TGF-β/Smad signaling pathway - Jiaming Li; Tingjin Zheng; Yingzhi Xu; Mengcha Tian; Liangpan Shi; Jintu Chen; Tian Li; Zhishan Zhang (Tissue and Cell, 2025)

A NH2-UiO-66-TiO2/Al2O3 hollow ceramic membrane with an enhanced photocatalytic oxidation performance of NO - Wenjuan Yang; Wenli Liu; Yuanbo Song; Yangyang Wang; Yanbin Yun; Guicheng Liu; Chang Li; Jiaming Mao; Jia Liu; Meng Li; Chunyun Zhou; Manxiang Wang; et al. (Journal of Environmental Chemical Engineering, 2025)

An artificial intelligence and blockchain technology-based data management framework for multicenter randomized controlled trials - Dongyuan Yun; Xiaohang Wu; Xi Chen; Yahan Yang; Yuanjun Shang; Shaopeng Liu; Dinesh Visva Gunasekeran; Duoru Lin; Lixue Liu; Lanqin Zhao; Wenben Chen; Jingjing Chen; et al. (Science Bulletin, 2025)

VCU-Net: a vascular convolutional network with feature splicing for cerebrovascular image segmentation - Mengxin Li; Fan Lv; Jiaming Chen; Kunyan Zheng; Jingwen Zhao (Medical & Biological Engineering & Computing, 2025)

High performance two photon polymerization resin designed for sub-micron precision and millimeter scale structure manufacturing - Jiaming Hu; Yang Gao; Lukun Wu; Bowen Zheng; Ning Li; Kai Du; Jing Li; Shuai Zhang (Chemical Engineering Journal, 2025)

Integrating UAV, UGV and UAV-UGV collaboration in future industrialized agriculture: Analysis, opportunities and challenges - Zhigang Ren; Han Zheng; Jian Chen; Tao Chen; Pengyang Xie; Yunzhe Xu; Jiaming Deng; Huanzhe Wang; Mingjiang Sun; Wenchi Jiao (Computers and Electronics in Agriculture, 2024)

The energy system transition pathway towards carbon reduction using a model-coupling approach - Jiali Zheng; Xiaoqing Hou; Jiaming Yang; Lianyang Jiao; D’Maris Coffman; Shouyang Wang (Global Environmental Change, 2024)

Electroactive supramolecular nanoprobes for electrochemical detection of rituximab in non-Hodgkon’s lymphoma patients - Zhiwei Chen; Zheng Zhao; Jiaming Yuan; Qiaoxuan Zhang; Yufeng Wu; Qingjin Wu; Yuheng Liao; Jia-Huan Qu; Ning Gan; Zhengjin Jiang; Qiqin Wang (Chemical Engineering Journal, 2024)

Trajectory tracking PID passivity-based control of spacecraft formation flying around Sun-Earth L2 point in the port-Hamiltonian framework - Jiaming Wang; Qingrui Zhou; Wei Zheng; Jingdong Diao (Advances in Space Research, 2024)

A hybrid PM2.5 interval concentration prediction framework based on multi-factor interval decomposition reconstruction strategy and attention mechanism - Jiaming Zhu; Lili Niu; Peng Zheng; Huayou Chen; Jinpei Liu (Atmospheric Environment, 2024)

Assessing geological hazard susceptibility and impacts of climate factors in the eastern Himalayan syntaxis region - Jiaming Yao; Yanbing Wang; Teng Wang; Beibei Zhang; Yuming Wu; Xin Yao; Zheng Zhao; Shu Zhu (Landslides, 2024)

The relationship between repeated impacts and CAI strength of sandwich structure considering different impactor shape in individual impact - Keyu Zhu; Xitao Zheng; Jiaming Sun; Guoyue Wang; Leilei Yan (Engineering Structures, 2024)

Thermal inactivation kinetics of Listeria monocytogenes in milk under isothermal and dynamic conditions - Xiang Wang; Jiaming Zheng; Linyin Luo; Yi Hong; Xiaofeng Li; Yuqi Zhu; Yufan Wu; Li Bai (Food Research International, 2024)

A dual amplification-based CRISPR/Cas12a biosensor for sensitive detection of miRNA in prostate cancer - Yuqing Zhu; Xiaohe Zheng; Shujun Zhou; Wenjing Xiao; Xiaorui Sun; Jianming Zhou; Feiyang Qian; Tenghua Zhang; Yan Sheng; Jiaming Hu (Analytica Chimica Acta, 2023)

Rapid adaptive evolution of Bacillus coagulans to undetoxified corncob hydrolysates for lactic acid production and new insights into its high phenolic degradation - Jiaming Fu; Zijie Wang; Hongcheng Miao; Chang Yu; Zhaojuan Zheng; Jia Ouyang (Bioresource Technology, 2023)

The carbon reduction effects of stepped carbon emissions trading and carbon capture and storage on hybrid wind-PV-thermal- storage generation operating systems - Yongmei Wei; Xinyu Wang; Jin Zheng; Yihong Ding; Jiaming He; Jian Han (Environmental Science and Pollution Research, 2023)

CRISPR-Cas12a powered multifunctional DNA nanodumbbell lock biosensor for multiple molecular detection - Yuqing Zhu; Xiaohe Zheng; Rui Zhu; Hongrui Zhao; Hongli Zhai; Feiyang Qian; Tenghua Zhang; Zihui Xie; Silan Liu; Bowen Jiang; Yan Sheng; Jiaming Hu (Chemical Engineering Journal, 2023)

An improved spatial case-based reasoning considering multiple spatial drivers of geographic events and its application in landslide susceptibility mapping - Zheng Zhao; Jianhua Chen; Jiaming Yao; Kaihang Xu; Yangyang Liao; Huawei Xie; Xianxia Gan (CATENA, 2023)

Selection and truncation of aptamers as fluorescence sensing platforms for selective and sensitive detection of nitrofurazone - Xu Wen; Xueling Yan; Xiaoling Zheng; Qiming Kou; Lulan Yang; Jiaming Tang; Xingyue Chen; Yong Xie; Tao Le (Analytica Chimica Acta, 2023)

Hepatoprotective Effects of Taurine Against Cadmium-Induced Liver Injury in Female Mice - Jiaming Zheng; Guobin Qiu; Yewen Zhou; Kezhe Ma; Sheng Cui (Biological Trace Element Research, 2023)

Hydrogenation of biomass pyrolysis oil using enhanced reduction catalytic capacity cellular by expressing excavated carbonyl reductase - Chongyang Bu; Hui Qiao; Lihua Zou; Yuanming Tao; Jiaming Fu; Chao Liu; Zhaojuan Zheng; Jia Ouyang (Fuel, 2023)

Microbially driven fate of terrigenous particulate organic matter in oceans - Lianbao Zhang; Mingming Chen; Yue Zheng; Jianning Wang; Xilin Xiao; Xiaowei Chen; Chen Hu; Jiaming Shen; Jihua Liu; Kai Tang; Dapeng Xu; Qiang Shi; et al. (Limnology and Oceanography, 2023)
A long‐standing enigma in oceanography is why terrestrial organic matter is “missing” in the global ocean, despite the considerable discharge into it every year. Although some explanations, such as mineralogical composition, hydrodynamic processes, and priming effect, have been proposed, we hypothesize that the essential mechanism behind the missing organic matter is microbial processing, for which the underlying coupled geochemical, molecular, and genetic evidence is unknown. An ultra‐large‐volume, long‐term river–seawater stratified simulation system was constructed to unravel the microbially driven fate of terrigenous particulate organic matter (POM) in oceans. Analysis of combining the molecular with POM chemical composition data suggests that Bacteroidetes could act as pioneers in the processing of terrigenous POM in oceans, degrading high‐molecular‐weight, high‐carbon compounds such as polysaccharides. Remaining low‐molecular‐weight nitrogenous organic matter is subsequently degraded by Planctomycetes and Proteobacteria. Isotopic signals show that this preferential degradation causes a distinct “aging” effect of POM, and along with nitrification enhanced by remineralization, causes a decrease in the POM C : N ratio. Degradation of terrigenous POM and bacterial biomass biosynthesis leads to positive deviations in δ 15 N and δ 13 C. Relatively refractory hydrocarbons, aromatic compounds, and phenols are accumulated by microbial processes in this system. This study provides mechanistic insights into the missing chemical and isotopic signals and microbially driven fate of terrigenous POM in the ocean, with important implications for how riverine material input affects marine carbon and nitrogen cycling.

Mapping of a major QTL for salinity tolerance at the bud burst stage in rice (Oryza sativa L) using a high-density genetic map - Lei Lei; Zhenghong Han; Bowen Cui; Luomiao Yang; Hualong Liu; Jingguo Wang; Hongwei Zhao; Wei Xin; Xianwei Li; Jiaming Li; Jingnan Cui; Shanbin Xu; et al. (Euphytica, 2021)

Role of rgsA in Oxidative Stress Resistance in Pseudomonas aeruginosa - Shuyi Hou; Jiaqin Zhang; Xiaobo Ma; Qiang Hong; Lili Fang; Gangsen Zheng; Jiaming Huang; Yingchun Gao; Qiaoli Xu; Xinguo Zhuang; Xiuyu Song (Current Microbiology, 2021)

Influences of ABC transporter and CYP3A4/5 genetic polymorphisms on the pharmacokinetics of lenvatinib in Chinese healthy subjects - Jiaming Li; Xiaoqian Wang; Chen Ning; Zhaoyu Wang; Yao Wang; Ming Zheng; Siliang Zhang; Yang Lu; Yongjie Zhang; Ning Li; Xijing Chen; Di Zhao (European Journal of Clinical Pharmacology, 2020)

High spatio-temporal heterogeneity of carbon footprints in the Zhejiang Province, China, from 2005 to 2015: implications for climate change policies - Sheng Zheng; Jiaming Shan; Ramesh P. Singh; Yuzhe Wu; Jiachen Pan; Yueshe Wang; Eric Lichtfouse (Environmental Chemistry Letters, 2020)

Genetic mapping and molecular marker development for Pi65(t), a novel broad-spectrum resistance gene to rice blast using next-generation sequencing - Wenjing Zheng; Yan Wang; Lili Wang; Zuobin Ma; Jiaming Zhao; Ping Wang; Lixia Zhang; Zhiheng Liu; Xiaochun Lu (Theoretical and Applied Genetics, 2016)

A Highly Sensitive Solid Substrate Room Temperature Phosphorimetry for Carbaryl Detection Based on its Activating Effect on NaIO4 Oxidizing Fluorescein - Jiaming Liu; Qitong Huang; Zhen-bo Liu; Xiaofeng Lin; Li-Hong Zhang; Chang-Qing Lin; Zhi-Yong Zheng (Journal of Fluorescence, 2014)

AtRabD2b, a Functional Ortholog of the Yeast Ypt1, Controls Various Growth and Developmental Processes in Arabidopsis - Fang Wang; Chao Liu; Chen Wei; Yuhai Cui; Qian Zheng; Jiaming Zhang; Jiangsheng Wu; Kede Liu (Plant Molecular Biology Reporter, 2012)